2014
DOI: 10.2458/56.17503
|View full text |Cite
|
Sign up to set email alerts
|

14C Measurements Elucidate Isotopic Differences between Nails and Hair in Modern Humans

Abstract: In forensic sciences, radiocarbon found in modern human nails and hair is evaluated to determine the year of death. However, 14 C analyses presented herein of fingernails and hair from the same infant demonstrated 14 C values of hair that were lower than would be expected (e.g. depleted relative to the fingernails by at least 10‰). These results prompted a series of 14 C measurements on infant hair strands, fingernails, and infant shampoo, which suggested the presence of C contamination due to cosmetic product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Previous time‐series experiments using 14 C‐AMS to address the deposition and accumulation effects of shampoo contaminants in scalp‐hair on an infant indicated that, once the contaminant was deposited into the hair, it remained for a period of several months . Since previous C/N ratios from Subject B were also anomalous (as mentioned above), we expected to see the same phenomenon, although all the keratinaceous samples for this study were taken 1 year apart.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Previous time‐series experiments using 14 C‐AMS to address the deposition and accumulation effects of shampoo contaminants in scalp‐hair on an infant indicated that, once the contaminant was deposited into the hair, it remained for a period of several months . Since previous C/N ratios from Subject B were also anomalous (as mentioned above), we expected to see the same phenomenon, although all the keratinaceous samples for this study were taken 1 year apart.…”
Section: Resultsmentioning
confidence: 60%
“…Isotopic analyses and C/N determinations were carried out on fingernails and hair samples (scalp and body), and the results are listed in Table . Previously, the δ 13 C values from the scalp‐hair of Subject B were lower than those of the fingernail by 0.8‰ on average, while the atomic C/N values ranged from 4.0 to 4.6 (scalp to hair‐tip) with a total %C of 45.8–50.4 . An apparent loss on the %N was also observed, probably due to hair protein alterations at the molecular level, an issue already reported by others .…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations